Model Matematika Penyebaran Perilaku Online Compulsive Buying: Literature Review - Niati Asma; Icih Sukarsih; Didi Suhaedi (Jurnal Riset Matematika, 2025)
Abstract. Online compulsive buying (OCB) is an excessive consumption phenomenon that has been increasingly prevalent in the digital era. This behavior negatively impacts not only individual financial well-being but also mental health, including increased anxiety, stress, and impulse control disorders. Various psychological and social factors, such as Fear of Missing Out (FoMO), self-control, peer influence, and social media exposure, have been proven to play essential roles in triggering and facilitating OCB behavior. This literature review explores the dynamics of OCB behavior dissemination and its implications, as well as the role of mathematical modeling as an innovative approach to study and support effective intervention efforts. The review results indicate that interventions targeting the enhancement of self-control and stress management can significantly reduce the prevalence of OCB. Moreover, this article discusses mathematical models that can simulate the spread and control of compulsive buying behavior within digital populations. However, further development of more realistic models and validation using empirical data is still necessary. This review emphasizes the need for a multidisciplinary approach that integrates psychology, mathematics, and information technology to design more targeted, measurable, and sustainable OCB prevention strategies in an increasingly digital society. Abstrak. Perilaku belanja online kompulsif (online compulsive buying-OCB) merupakan fenomena konsumsi berlebihan yang semakin meningkat di era digital. Perilaku ini tidak hanya berdampak negatif pada aspek finansial individu, tetapi juga memengaruhi kesehatan mental, termasuk meningkatkan kecemasan, stres, dan gangguan kontrol impuls. Berbagai faktor psikologis dan sosial, seperti Fear of Missing Out (FoMO), kontrol diri (self-control), serta pengaruh teman sebaya dan media sosial, terbukti memainkan peran penting dalam memicu dan memfasilitasi penyebaran perilaku OCB. Kajian literatur ini mengulas dinamika penyebaran perilaku OCB dan implikasinya, serta peran pemodelan matematika sebagai pendekatan inovatif untuk mengkaji serta mendukung upaya intervensi yang efektif. Hasil review menunjukkan bahwa intervensi yang menargetkan peningkatan kontrol diri dan pengelolaan stres secara signifikan dapat mengurangi prevalensi OCB. Selain itu, artikel ini membahas berbagai model matematika yang mampu mensimulasikan penyebaran dan pengendalian perilaku compulsive buying pada populasi digital. Meskipun demikian, pengembangan model yang lebih realistis dan validasi berbasis data empiris masih diperlukan. Kajian ini menekankan pentingnya pendekatan multidisiplin yang mengintegrasikan psikologi, matematika, dan teknologi informasi untuk merancang strategi pencegahan OCB yang lebih tepat sasaran, terukur, dan berkelanjutan di tengah masyarakat digital yang terus berkembang.